Composite antibacterial and antiviral plate and preparation method of composite antibacterial and antiviral agent
By uniformly dispersing nano-silver-zinc composite ions and other components on the plate, combining porous nanostructures and impregnated decorative paper technology, the existing antibacterial and anti-elution performance are solved, and a wider spectrum and long-lasting anti-bacterial and anti-viral effect is achieved.
Patent Information
- Application Number
- CN202411340345.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing antibacterial and antiviral plates have limited antibacterial and antiviral ranges, and cannot widely inhibit a variety of bacteria. The antibacterial and antiviral effect will weaken over time, and the anti-elution performance is poor.
By uniformly dispersing nano-silver-zinc composite ions, polyhexamethyleneguanidine hydrochloride, chitosan quaternary ammonium salt and other components in the porous nanostructures, a composite antibacterial and antiviral agent is formed, and it is applied to the plate by impregnating decorative paper technology.
It significantly improves the antibacterial and antiviral performance of the sheet, extends its antibacterial and antiviral aging life, and increases performance by 30% on a single antibacterial or antiviral function.
Smart Images

Figure CN119589767A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antibacterial and antiviral plates, and in particular to a preparation method of a composite antibacterial and antiviral plate and a composite antibacterial and antiviral agent. Background Art
[0002] Antibacterial and antiviral panels are panels that have the function of inhibiting the growth and reproduction of bacteria and viruses. Their technical background mainly stems from people's pursuit of a healthy living environment. With the improvement of people's health awareness and the concern about the spread of bacteria and viruses in indoor environments, the research and development of panels with antibacterial and antiviral properties has become an important direction in the field of materials. The current research and development of antibacterial and antiviral panels mainly relies on a variety of technical means, such as nano-silver ion technology, which evenly disperses nano-scale silver ions in the panels and uses their powerful antibacterial and antiviral properties to destroy the cell membrane structure of microorganisms and inhibit their growth and reproduction. Natural plant extract technology: using antibacterial and antiviral active ingredients of Chinese herbal medicines such as wormwood, isatis root, honeysuckle or natural plant extracts such as tea tree essential oil and allicin, and adding them to the panels; ion exchange technology: introducing zinc ions, copper ions and other ions with antibacterial and antiviral effects into the panels through ion exchange methods. These ions can affect the physiological functions of microorganisms; photocatalytic technology: coating photocatalysts such as titanium dioxide on the surface of the panels, using light conditions to produce strong oxidizing substances to decompose the cell walls and protein structures of bacteria and viruses.
[0003] However, the above-mentioned existing technologies have a limited antibacterial and antiviral range. Different technologies may only be effective against specific types of bacteria or viruses and cannot widely inhibit multiple pathogens. Over time, the antibacterial and antiviral effects will continue to weaken, and some coatings will peel off or even fall off, resulting in a decrease in antibacterial and antiviral performance. Nano silver ions, as broad-spectrum antibacterial agents, are not effective against all types of bacteria and viruses. Single-ion antibacterial agents have poor anti-elution properties and are easily eluted from the surface of the board. After multiple washes, their protective ability will be greatly attenuated. The anti-mildew performance of silver ions is also limited. For some environments with high requirements for mildew resistance, other anti-mildew measures or materials with better mildew resistance are required. It can be seen that we urgently need a composite antibacterial and antiviral board. Summary of the invention
[0004] In view of the above-mentioned technical deficiencies, the purpose of the present invention is to provide a composite antibacterial and antiviral board and a composite antibacterial and antiviral agent, by adding a composite reagent with antiviral function into impregnated paper to prepare an impregnation liquid, strengthening the antibacterial and antiviral function through the composite of multiple antibacterial ions, and wrapping the nanoparticles through a porous nanostructure so that they are more evenly dispersed in the carrier, so that the final formed decorative panel has significant antibacterial and antiviral properties after pressing.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a composite antibacterial and antiviral board material, comprising two substrates, a balancing layer is provided at one end of the two substrates, an adhesive is provided between the two substrates and the two balancing layers, and an antibacterial and antiviral impregnated decorative paper is provided between the two balancing layers.
[0006] The invention discloses a composite antibacterial and antiviral agent composition of a composite antibacterial and antiviral plate. The composite antibacterial and antiviral agent comprises the following components: nano silver zinc composite ion, polyhexamethylene guanidine hydrochloride, auxiliary antiviral agent, chitosan quaternary ammonium salt, stabilizer propylene glycol, nano porous structure aluminum silicate, and solvent deionized water. The composite antibacterial and antiviral agent composition is as follows: nano silver zinc composite ion solution, content of 2% to 5%, polyhexamethylene guanidine hydrochloride, content of 10% to 20%, auxiliary antiviral agent and chitosan quaternary ammonium salt content of 10% to 20%, stabilizer propylene glycol content of 5% to 10%, nano porous structure aluminum silicate content of 10% to 20%, and solvent deionized water, content of which is the remainder.
[0007] A method for preparing a nano silver-zinc composite ion solution in a composite antibacterial and antiviral agent of a composite antibacterial and antiviral plate comprises the following steps: preparing silver nitrate, zinc sulfate, ammonium carbonate, ammonium bicarbonate, deionized water, and anhydrous ethanol to prepare a silver-zinc precursor, dissolving silver nitrate in deionized water to obtain a silver nitrate solution, dissolving zinc sulfate in deionized water to obtain a zinc sulfate solution, dissolving ammonium carbonate and ammonium bicarbonate in deionized water to obtain a precipitation solution, further slowly dropping the silver nitrate solution and the zinc sulfate solution into a precipitant solution while stirring to react and generate a silver-zinc precursor precipitate, and precipitating the silver-zinc precursor precipitate with deionized water and anhydrous ethanol for 3 minutes. The method comprises the steps of: washing the mixture for 2 hours to 6 hours to remove impurities, and then drying the washed precipitate in a vacuum drying oven to obtain a dried silver-zinc precursor powder; further, adding the dried silver-zinc precursor powder to deionized water, stirring evenly, and obtaining a silver-zinc precursor solution; further, subjecting the silver-zinc precursor solution to ultrasonic treatment to uniformly disperse the silver-zinc precursor in the solution; heating the silver-zinc precursor solution after ultrasonic treatment to decompose the silver-zinc precursor to generate a nano-silver-zinc composite ion solution; cooling the generated nano-silver-zinc composite ion solution, and then diluting the solution with deionized water to obtain a nano-silver-zinc composite ion solution of a desired concentration.
[0008] A method for preparing polyhexamethyleneguanidine hydrochloride in a composite antibacterial and antiviral agent of a composite antibacterial and antiviral plate comprises the following steps: hexamethylenediamine and 36% hydrochloric acid are mixed in a certain proportion, the molar ratio of hexamethylenediamine to hydrochloric acid can be controlled between 1:2 and 1:2.5; during the mixing process, hydrochloric acid is slowly added to avoid violent reaction and local overheating; the mixed solution is heated to an appropriate temperature, the temperature is controlled between 60 and 80°C, the reaction time can be controlled within 3 to 5 hours, after the reaction is completed, the product is cooled, and then impurities are removed by 3 to 6 suction filtrations and 5 to 10 deionized water washings; the product is dried to obtain polyhexamethyleneguanidine hydrochloride.
[0009] A method for preparing chitosan quaternary ammonium salt in a composite antibacterial and antiviral agent of a composite antibacterial and antiviral plate comprises the following steps: adding chitosan, formaldehyde, formic acid and distilled water in sequence into a three-necked flask equipped with a condenser, wherein the mass ratio of chitosan, formaldehyde, formic acid and distilled water is 1:5:5:20; starting a magnetic stirrer at a speed of 100-700 r / min; reacting at 50-80° C. for 72 hours to obtain a light yellow solution; and subjecting the obtained light yellow solution to reduced pressure distillation at 0.05-0.1 MPa and 45-65° C. for 30 minutes. After that, the pH is adjusted to 10-13 with an alkaline solution to form a large amount of gel, followed by vacuum filtration at 0.05-0.1MPa, washing with anhydrous ethanol to neutrality to obtain a light yellow gel-like substance, drying at 60-120°C, grinding into a light yellow powder, dissolving the light yellow powder with an acidic solution, and continuing to add an acidic solution to adjust the pH to 3-5, at this time a white precipitate can be obtained, washing with distilled water for 5-10 times, freeze-drying at -30 to -60°C, and grinding the dried product to obtain chitosan quaternary ammonium salt.
[0010] A method for preparing nano aluminosilicate in a composite antibacterial and antiviral agent of a composite antibacterial and antiviral plate comprises the following steps: mixing tetraethyl orthosilicate, tetrapropylammonium hydroxide, sodium aluminate and water in a mass ratio of 45:5:1:120, placing the mixed system in a high-temperature hydrothermal reactor, wherein the volume of the mixed system accounts for 80%-85% of the total volume of the reactor, raising the temperature in the reactor to 175-185°C at a heating rate of 4-6°C / min, and keeping the temperature for 4-6 h, after natural cooling, a solid-liquid mixed system is obtained, the solid-liquid mixed system is centrifuged at a rotation speed of 8000-10000 rpm for 5-10 min to obtain a sol clear liquid, the sol clear liquid is spin-coated on a clean glass surface at a spin-coating speed of 2000-3000 rpm, the glass system coated with the sol is dried, sintered at 500-550° C. for 1-3 h, and after natural cooling, a nanoporous aluminosilicate film is obtained, which is ground to obtain a nano aluminosilicate powder.
[0011] A method for preparing a composite antibacterial and antiviral agent for a composite antibacterial and antiviral plate comprises the following steps:
[0012] S1. Accurately weigh the prepared nano silver-zinc composite ion solution, polyhexamethyleneguanidine hydrochloride, chitosan quaternary ammonium salt, and nano aluminum silicate according to the formula ratio;
[0013] S2, add to an appropriate amount of ionized water, stir at 60-80°C and 500-800 r / min for 240-300 min to fully dissolve and mix the components;
[0014] S3, using a membrane method to filter the prepared composite product to remove impurities;
[0015] S4, sterilizing the filtered solution to obtain the finished product of the composite antibacterial and antiviral agent.
[0016] A method for preparing antibacterial and antiviral impregnated decorative paper of a composite antibacterial and antiviral sheet material, the method for preparing the antibacterial and antiviral impregnated decorative paper comprising:
[0017] S1, add 5% by mass of curing agent to the melamine formaldehyde resin for impregnation with a solid content of 55% and a pH of 9.5, and stir quickly and evenly;
[0018] S2. The decorative paper base paper is driven by the rotating roller of the impregnation machine. The rolling speed of the roller is 15 m / min. The decorative paper base paper is kept completely immersed in the first melamine formaldehyde resin impregnation. The base paper is then transferred to a drying oven. The oven temperature is adjusted to 110° C.
[0019] S3, the rolling shaft is driven to the second impregnation tank, the antibacterial and antiviral agent is added to the melamine formaldehyde resin at a mass ratio of 0.5%, and the mixture is quickly stirred to be uniform, and the antibacterial and antiviral melamine formaldehyde resin for impregnation is prepared, the amount of glue is controlled to be 120g, and the decorative paper is kept completely immersed in the second impregnation, and then the mixture is driven to the drying oven for the second drying, the oven temperature is 130°C, and the mixture is dried for 10 minutes until the pre-curing degree is 40%;
[0020] S4. After the second drying, adjust the oven temperature, dehumidify and cool to 50° C., control the total weight gain rate after two dips and drying to 110% of the base paper, cut and package according to the required size, and obtain antibacterial and antiviral decorative paper.
[0021] A method for preparing a substrate of a composite antibacterial and antiviral plate, the method for preparing the substrate comprising:
[0022] S1, select blockboard as base material, moisture content 7.5%, specification 2440mm*1220mm*17mm, balance layer selects technical wood veneer, thickness 0.50mm;
[0023] S2, using the joinery board as the base material and the technical wood veneer as the balance layer, two finishing processes, the primary lamination method and the secondary lamination method, were used to prepare the antibacterial and antiviral impregnated film paper veneer joinery board;
[0024] S3, 一 The second lamination process uses a glue spreading machine to coat the blockboard on both sides, with a glue spreading amount of 220-230g / ㎡ on each side, and the upper and lower sides are pressed with high-tech wood veneers, with a hot pressing temperature of 125℃, a hot pressing time of 9-10min, and a unit hot pressing pressure of 0.65-0.7MPa; after the hot pressing is completed, the antibacterial and antiviral impregnated film paper veneer is pressed, with a hot pressing temperature of 125-130℃, a hot pressing time of 6-7min, and a unit hot pressing pressure of 0.60-0.65MPa;
[0025] S4, secondary lamination process, firstly, the antibacterial and antiviral impregnated adhesive paper and poplar veneer are hot pressed on one side, the hot pressing temperature is 190-200℃, the hot pressing pressure is 2.4MPa, and the hot pressing time is 15-20s; the glue machine coats urea-formaldehyde resin on both sides of the blockboard, the glue amount on each side is 220-230g / ㎡, the upper and lower layers of adhesive paper / poplar veneer composite are pressed, the hot pressing temperature is 90-95℃, the hot pressing time is 600s, and the unit hot pressing pressure is 0.65MPa.
[0026] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0027] The present invention forms a novel composite antibacterial and antiviral agent by combining a variety of antibacterial and antiviral technologies. Compared with general antibacterial or antiviral plates, the antibacterial and antiviral plates have a synergistic effect, increasing the performance of a single antibacterial or antiviral function by 30%. At the same time, the present invention uses synergistic enhancement and porous nanostructures to make the antibacterial and antiviral components more evenly dispersed in the system, and reduces the consumption of active ingredients through ion replacement, thereby achieving the effect of sustained release of active ingredients and extending its antibacterial and antiviral time-effect life. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a structural schematic diagram of the present invention;
[0029] Figure 2 It is a structural schematic diagram of the present invention;
[0030] Among them: 1. Base material; 2. Balancing layer; 3. Adhesive; 4. Antibacterial and antiviral impregnated decorative paper. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The present invention provides the following technical solutions:
[0033] Embodiment 1
[0034] An embodiment of a composite antibacterial and antiviral agent for a composite antibacterial and antiviral plate,
[0035] Reference Figure 1 ,
[0036] The composite antibacterial and antiviral agent comprises the following components: nano silver zinc composite ion, polyhexamethylene guanidine hydrochloride, auxiliary antiviral agent, chitosan quaternary ammonium salt, stabilizer propylene glycol, nano porous structure aluminum silicate, solvent deionized water, nano silver zinc composite ion solution, content of 2% to 5%, polyhexamethylene guanidine hydrochloride, content of 10% to 20%, auxiliary antiviral agent, chitosan quaternary ammonium salt content of 10% to 20%, stabilizer propylene glycol content of 5% to 10%, nano porous structure aluminum silicate, content of 10% to 20%, solvent deionized water, content of which is the remainder;
[0037] The following steps are involved:
[0038] S1. Accurately weigh the prepared nano silver-zinc composite ion solution, polyhexamethyleneguanidine hydrochloride, chitosan quaternary ammonium salt, and nano aluminum silicate according to the formula ratio;
[0039] S2, add to an appropriate amount of ionized water, stir at 60-80°C and 500-800 r / min for 240-300 min to fully dissolve and mix the components;
[0040] S3, using a membrane method to filter the prepared composite product to remove impurities;
[0041] S4. Sterilize the filtered solution to obtain a finished composite antibacterial and antiviral agent.
[0042] Through the above technical scheme, the overall steps are: S1, add 5 parts by mass of 10% nano silver-zinc composite ion solution to 100 parts by mass of deionized water, put it into a magnetic stirrer and mix it evenly, the stirring speed is 300r / min, and the stirring is continued for 15 minutes until the solution is completely mixed.
[0043] S2. Slowly drop hydrochloric acid into hexamethylenediamine at a molar ratio of 1:2, heat the mixed liquid to 60°C, react at a constant temperature for 3 hours, filter after cooling, wash with deionized water, and obtain polyhexamethyleneguanidine hydrochloride after drying. Weigh 10 parts by mass of polyhexamethyleneguanidine hydrochloride, add sufficient deionized water, and continue stirring until the polyhexamethyleneguanidine hydrochloride is completely dissolved.
[0044] S3. Chitosan, formaldehyde, formic acid and distilled water were added into a three-necked flask equipped with a condenser in sequence, wherein the mass ratio of chitosan, formaldehyde, formic acid and distilled water was 1:5:5:20. A magnetic stirrer was turned on at a speed of 500 r / min. The mixture was reacted at 50°C for 72 h. The obtained light yellow solution was distilled under reduced pressure at 0.1 MPa and 65°C for 30 min. The pH value was adjusted to 11 with an alkaline solution to form a large amount of gel. The mixture was then vacuum filtered at 0.1 MPa and collected. The mixture was washed with anhydrous ethanol until neutral to obtain a light yellow gel-like substance, which was dried at 90°C and ground into a light yellow powder. The light yellow powder was dissolved with an acidic solution, and the acidic solution was continued to be added to adjust the pH to 3. At this time, a white precipitate was obtained, which was washed with distilled water for 5 times and freeze-dried at -30°C. The dried product was ground to obtain chitosan quaternary ammonium salt. 10 parts by mass of chitosan quaternary ammonium salt were weighed, and sufficient deionized water was added, and stirring was continued until the chitosan quaternary ammonium salt was completely dissolved.
[0045] S4. After tetraethyl orthosilicate, tetrapropylammonium hydroxide, sodium aluminate and water are stirred and mixed at a mass ratio of 45:5:1:120, the mixed system is placed in a high-temperature hydrothermal reactor, wherein the volume of the mixed system accounts for 80% of the total volume of the reactor, the temperature in the reactor is raised to 175°C at a heating rate of 4°C / min, and the mixture is kept warm for 4 hours. After natural cooling, a solid-liquid mixed system is obtained, the solid-liquid mixed system is centrifuged at a rotation speed of 8000 rpm for 5 minutes to obtain a sol clear liquid, and the sol clear liquid is spin-coated on a clean glass surface at a spin-coating speed of 2000 rpm. After drying the glass system coated with the sol, it is sintered at 500°C for 1 hour, and after natural cooling, a nanoporous aluminosilicate film is obtained, and nanoporous aluminosilicate powder is obtained after grinding. 10 parts by mass of the nanoporous aluminosilicate are weighed, sufficient deionized water is added, and stirring is continued until the nanoporous aluminosilicate is completely dissolved.
[0046] S5. Add the above-prepared nano-silver-zinc composite ion solution, polyhexamethyleneguanidine hydrochloride solution, chitosan quaternary ammonium salt solution, and nano-aluminum silicate solution to an appropriate amount of ion water, heat to 60°C, stir at 500r / min for 240min, filter the prepared composite product using a thin film method to remove impurities, and sterilize the prepared composite solution by ultraviolet radiation at a wavelength of 254nm for 30min to obtain a composite antibacterial and antiviral agent.
[0047] S6. Add 5% by weight of curing agent to the melamine formaldehyde resin for impregnation, with a solid content of 55% and a pH of 9.5, and stir quickly and evenly.
[0048] S7. The decorative paper base paper is driven by the rotating roller of the impregnation machine. The rolling speed of the roller is 15 m / min. The decorative paper base paper is kept completely immersed in the first melamine formaldehyde resin impregnation. The base paper is then transferred to a drying oven. The oven temperature is adjusted to 110°C.
[0049] S8. The rolling shaft is driven to the second impregnation tank, and the antibacterial and antiviral agent is added to the melamine formaldehyde resin at a mass ratio of 0.5%. The mixture is quickly stirred evenly to prepare the antibacterial and antiviral melamine formaldehyde resin for impregnation. The amount of glue is controlled to be 120g, and the decorative paper is kept completely immersed in the second impregnation. The decorative paper is then driven to the drying oven for the second drying. The oven temperature is 130°C, and the process is dried for 10 minutes until the pre-curing degree is 40%.
[0050] S9. After the second drying, adjust the oven temperature, dehumidify and cool to 50° C., control the total weight gain rate after two dips and drying to 110% of the base paper, cut and package according to the required size, and obtain antibacterial and antiviral decorative paper.
[0051] S10. Use blockboard as base material with a moisture content of 7.5% and a specification of 2440mm*1220mm*17mm. The balance layer is made of high-tech wood veneer with a thickness of 0.50mm and a curing period of 7 days.
[0052] S11. Use a glue spreading machine to double-sided coat the blockboard substrate, with a glue spreading amount of 220g / ㎡ on each side, and press the high-tech wood veneer on the upper and lower sides, with a hot pressing temperature of 125℃, a hot pressing time of 10min, and a unit hot pressing pressure of 0.65MPa; after the hot pressing is completed, press the antibacterial and antiviral impregnated film paper veneer, with a hot pressing temperature of 136℃, a hot pressing time of 4min, and a unit hot pressing pressure of 0.6MPa.
[0053] Embodiment 2
[0054] An embodiment of a nano silver-zinc composite ion solution in a composite antibacterial and antiviral agent of a composite antibacterial and antiviral board
[0055] The preparation method of the nano silver-zinc composite ion solution is as follows: prepare silver nitrate, zinc sulfate, ammonium carbonate, ammonium bicarbonate, deionized water, and anhydrous ethanol to prepare a silver-zinc precursor, dissolve silver nitrate in deionized water to obtain a silver nitrate solution, dissolve zinc sulfate in deionized water to obtain a zinc sulfate solution, dissolve ammonium carbonate and ammonium bicarbonate in deionized water to obtain a precipitation solution, further, slowly dropwise add the silver nitrate solution and the zinc sulfate solution to the precipitant solution while stirring, react to generate a silver-zinc precursor precipitate, wash the silver-zinc precursor precipitate with deionized water and anhydrous ethanol for 3 to 6 times to remove impurities, The washed precipitate is then dried in a vacuum drying oven to obtain a dried silver-zinc precursor powder. The dried silver-zinc precursor powder is further added to deionized water and stirred evenly to obtain a silver-zinc precursor solution. The silver-zinc precursor solution is further subjected to ultrasonic treatment to uniformly disperse the silver-zinc precursor in the solution. The ultrasonically treated silver-zinc precursor solution is heated to decompose the silver-zinc precursor to generate a nanometer silver-zinc composite ion solution. The generated nanometer silver-zinc composite ion solution is cooled and then diluted with deionized water to obtain a nanometer silver-zinc composite ion solution of a desired concentration.
[0056] Embodiment 3
[0057] Embodiment of a method for preparing polyhexamethyleneguanidine hydrochloride in a composite antibacterial and antiviral agent of a composite antibacterial and antiviral board
[0058] The preparation method of polyhexamethyleneguanidine hydrochloride comprises the following steps: mixing hexamethylenediamine and 36% hydrochloric acid in a certain ratio, wherein the molar ratio of hexamethylenediamine to hydrochloric acid can be controlled between 1:2 and 1:2.5; during the mixing process, slowly adding hydrochloric acid to avoid violent reaction and local overheating; heating the mixed solution to an appropriate temperature, wherein the temperature is controlled between 60 and 80°C; and the reaction time can be controlled between 3 and 5 hours; after the reaction is completed, cooling the product, and then removing impurities by means of 3 to 6 times of suction filtration and 5 to 10 times of deionized water washing; and drying the product to obtain polyhexamethyleneguanidine hydrochloride.
[0059] Embodiment 4
[0060] Embodiment of a method for preparing chitosan quaternary ammonium salt in a composite antibacterial and antiviral agent of a composite antibacterial and antiviral plate
[0061] The preparation method of chitosan quaternary ammonium salt is as follows: chitosan, formaldehyde, formic acid and distilled water are sequentially added into a three-necked flask equipped with a condenser, wherein the mass ratio of chitosan, formaldehyde, formic acid and distilled water is 1:5:5:20, a magnetic stirrer is turned on, the speed is 100-700r / min, and the reaction is carried out at 50-80°C for 72 hours to obtain a light yellow solution, the obtained light yellow solution is subjected to reduced pressure distillation at 0.05-0.1MPa and 45-65°C for 30 minutes, and the pH value is adjusted to 50.5 with an alkaline solution. 10-13 to form a large amount of gel, followed by vacuum filtration at 0.05-0.1MPa, washing with anhydrous ethanol until neutral to obtain a light yellow gel-like substance, drying at 60-120°C, grinding into a light yellow powder, dissolving the light yellow powder with an acidic solution, continuing to add an acidic solution to adjust to a pH of 3-5, at which time a white precipitate can be obtained, washing with distilled water for 5-10 times, freeze-drying at -30 to -60°C, and grinding the dried product to obtain chitosan quaternary ammonium salt.
[0062] Embodiment 5
[0063] Embodiment of a method for preparing nano-aluminosilicate in a composite antibacterial and antiviral agent of a composite antibacterial and antiviral plate
[0064] The preparation method of nano-aluminosilicate is as follows: after tetraethyl orthosilicate, tetrapropylammonium hydroxide, sodium aluminate and water are stirred and mixed evenly at a mass ratio of 45:5:1:120, the mixed system is placed in a high-temperature hydrothermal reactor, wherein the volume of the mixed system accounts for 80%-85% of the total volume of the reactor, the temperature in the reactor is increased to 175-185°C at a heating rate of 4-6°C / min, and the temperature is kept for 4-6 hours. After natural cooling, a solid-liquid mixed system is obtained, the solid-liquid mixed system is centrifuged at a speed of 8000-10000rpm for 5-10 minutes to obtain a sol clear liquid, the sol clear liquid is spin-coated on a clean glass surface at a spin-coating speed of 2000-3000rpm, the glass system coated with the sol is dried, sintered at 500-550°C for 1-3 hours, and naturally cooled to obtain a nano porous aluminosilicate film, and the nano aluminosilicate powder is obtained after grinding.
[0065] Embodiment 6
[0066] An embodiment of a method for preparing antibacterial and antiviral impregnated decorative paper of a composite antibacterial and antiviral sheet material, the method for preparing the antibacterial and antiviral impregnated decorative paper 4 is:
[0067] S1, add 5% by mass of curing agent to the melamine formaldehyde resin for impregnation with a solid content of 55% and a pH of 9.5, and stir quickly and evenly;
[0068] S2. The decorative paper base paper is driven by the rotating roller of the impregnation machine. The rolling speed of the roller is 15 m / min. The decorative paper base paper is kept completely immersed in the first melamine formaldehyde resin impregnation. The base paper is then transferred to a drying oven. The oven temperature is adjusted to 110° C.
[0069] S3, the rolling shaft is driven to the second impregnation tank, the antibacterial and antiviral agent is added to the melamine formaldehyde resin at a mass ratio of 0.5%, and the mixture is quickly stirred to be uniform, and the antibacterial and antiviral melamine formaldehyde resin for impregnation is prepared, and the amount of glue is controlled to be 120g, and the decorative paper is kept completely immersed in the second impregnation, and then the mixture is driven to the drying oven for the second drying, and the oven temperature is 130°C, and the mixture is dried for 10 minutes until the pre-curing degree is 40%;
[0070] S4. After the second drying, adjust the oven temperature, dehumidify and cool to 50° C., control the total weight gain rate after two dips and drying to 110% of the base paper, cut and package according to the required size, and obtain antibacterial and antiviral decorative paper 4.
[0071] Embodiment 7
[0072] Embodiment of a method for preparing a composite antibacterial and antiviral board substrate
[0073] It comprises two substrates 1, one end of each of the two substrates 1 is provided with a balancing layer 2, adhesive 3 is provided between the two substrates 1 and the two balancing layers 2, and antibacterial and antiviral impregnated decorative paper 4 is provided between the two balancing layers 2;
[0074] The preparation method of substrate 1 is as follows:
[0075] S1, select blockboard substrate, moisture content 7.5%, specification 2440mm*1220mm*17mm, balance layer 2 selects technical wood veneer, thickness 0.50mm;
[0076] S2, using the joinery board as the base material and the technical wood veneer as the balance layer, two finishing processes, the primary lamination method and the secondary lamination method, were used to prepare the antibacterial and antiviral impregnated film paper veneer joinery board;
[0077] S3, 一 The second lamination process uses a glue spreading machine to coat the blockboard on both sides, with a glue spreading amount of 220-230g / ㎡ on each side, and the upper and lower sides are pressed with high-tech wood veneers, with a hot pressing temperature of 125℃, a hot pressing time of 9-10min, and a unit hot pressing pressure of 0.65-0.7MPa; after the hot pressing is completed, the antibacterial and antiviral impregnated film paper veneer is pressed, with a hot pressing temperature of 125-130℃, a hot pressing time of 6-7min, and a unit hot pressing pressure of 0.60-0.65MPa;
[0078] S4, secondary lamination process, firstly, the antibacterial and antiviral impregnated adhesive paper and poplar veneer are hot pressed on one side, the hot pressing temperature is 190-200℃, the hot pressing pressure is 2.4MPa, and the hot pressing time is 15-20s; the glue machine coats urea-formaldehyde resin on both sides of the blockboard, the glue amount on each side is 220-230g / ㎡, and the upper and lower layers of adhesive paper / poplar veneer composite are pressed, the hot pressing temperature is 90-95℃, the hot pressing time is 600s, and the unit hot pressing pressure is 0.65MPa
[0079] Through the above technical scheme, the preparation method of the composite antibacterial and antiviral plate and the composite antibacterial and antiviral agent includes the following steps:
[0080] S1. Add 3 parts by mass of 10% nano silver-zinc composite ion solution to 100 parts by mass of deionized water, put it on a magnetic stirrer and mix it evenly at a stirring speed of 300 r / min. Continue stirring for 15 minutes until the solution is completely mixed.
[0081] S2. Slowly drop hydrochloric acid into hexamethylenediamine at a molar ratio of 1:2.5, heat the mixed liquid to 60°C, react at a constant temperature for 3 hours, filter after cooling, wash with deionized water, and obtain polyhexamethyleneguanidine hydrochloride after drying. Weigh 10 parts by mass of polyhexamethyleneguanidine hydrochloride, add sufficient deionized water, and continue stirring until the polyhexamethyleneguanidine hydrochloride is completely dissolved.
[0082] S3. Chitosan, formaldehyde, formic acid and distilled water were added into a three-necked flask equipped with a condenser in sequence, wherein the mass ratio of chitosan, formaldehyde, formic acid and distilled water was 1:5:5:20. A magnetic stirrer was turned on at a speed of 500 r / min. The reaction was carried out at a temperature of 60°C for 72 hours. The obtained light yellow solution was distilled under reduced pressure at 0.1 MPa and 65°C for 30 minutes, and the pH was adjusted to 10 with an alkaline solution to form a large amount of gel, which was then vacuum filtered at 0.1 MPa. The mixture was washed with anhydrous ethanol until neutral to obtain a light yellow gel-like substance, which was dried at 90°C and ground into a light yellow powder. The light yellow powder was dissolved in an acidic solution, and the acidic solution was continued to be added to adjust the pH to 3.5. A white precipitate was obtained at this time, which was washed with distilled water for 5 times and freeze-dried at -30°C. The dried product was ground to obtain chitosan quaternary ammonium salt. 10 parts by mass of chitosan quaternary ammonium salt were weighed, and sufficient deionized water was added, and stirring was continued until the chitosan quaternary ammonium salt was completely dissolved.
[0083] S4. After tetraethyl orthosilicate, tetrapropylammonium hydroxide, sodium aluminate and water are stirred and mixed at a mass ratio of 45:5:1:120, the mixed system is placed in a high-temperature hydrothermal reactor, wherein the volume of the mixed system accounts for 70% of the total volume of the reactor, the temperature in the reactor is raised to 160°C at a heating rate of 5°C / min, and the mixture is kept warm for 4 hours. After natural cooling, a solid-liquid mixed system is obtained, the solid-liquid mixed system is centrifuged at a speed of 8000 rpm for 5 minutes to obtain a sol clear liquid, and the sol clear liquid is spin-coated on a clean glass surface at a spin-coating speed of 2000 rpm. After drying the glass system coated with the sol, it is sintered at 500°C for 1 hour, and after natural cooling, a nanoporous aluminosilicate film is obtained, and nanoporous aluminosilicate powder is obtained after grinding. 10 parts by mass of the nanoporous aluminosilicate are weighed, sufficient deionized water is added, and stirring is continued until the nanoporous aluminosilicate is completely dissolved.
[0084] S5. Add the above-prepared nano-silver-zinc composite ion solution, polyhexamethyleneguanidine hydrochloride solution, chitosan quaternary ammonium salt solution, and nano-aluminum silicate solution to an appropriate amount of ion water, heat to 50°C, stir at 500r / min for 200min, filter the prepared composite product using a thin film method to remove impurities, and sterilize the prepared composite solution by ultraviolet radiation at a wavelength of 254nm for 60min to obtain a composite antibacterial and antiviral agent.
[0085] S6. Add 5% by weight of curing agent to the melamine formaldehyde resin for impregnation, with a solid content of 55% and a pH of 10, and stir quickly and evenly.
[0086] S7. The decorative paper base paper is driven by the rotating roller of the impregnation machine. The rolling speed of the roller is 15 m / min. The decorative paper base paper is kept completely immersed in the first melamine formaldehyde resin impregnation. The base paper is then transferred to a drying oven. The oven temperature is adjusted to 110°C.
[0087] S8. The rolling shaft is driven to the second impregnation tank, and the antibacterial and antiviral agent is added to the melamine formaldehyde resin at a mass ratio of 0.5%. The mixture is quickly stirred evenly to prepare the antibacterial and antiviral melamine formaldehyde resin for impregnation. The amount of glue is controlled to be 120g, and the decorative paper is kept completely immersed in the second impregnation. The decorative paper is then driven to the drying oven for the second drying. The oven temperature is 120°C, and the drying is performed for 10 minutes until the pre-curing degree is 30%.
[0088] S9. After the second drying, adjust the oven temperature, dehumidify and cool to 55° C., control the total weight gain rate after two dips and drying to 120% of the base paper, cut and package according to the required size, and obtain antibacterial and antiviral decorative paper.
[0089] S10, choose blockboard as base material, with moisture content of 7.5%, specification of 2440mm*1220mm*17mm, and the balance layer shall be made of high-tech wood veneer, with thickness of 0.50mm.
[0090] S11. Hot press the antibacterial and antiviral impregnated adhesive paper and poplar veneer on one side at a temperature of 190°C, a pressure of 2.4 MPa and a time of 15 seconds. Apply urea-formaldehyde resin to both sides of the blockboard with a glue machine, with a glue amount of 230 g / m2 on each side. Press the antibacterial and antiviral adhesive paper / poplar veneer composite on the upper and lower layers at a temperature of 90°C, a time of 600 seconds and a unit pressure of 0.4 MPa.
[0091] Comparative Example:
[0092] The control sample is a melamine facing paper artificial board prepared by traditional methods. The base material is blockboard with a moisture content of 7.5% and a specification of 2440mm*1220mm*17mm. The balance layer is made of technological wood veneer with a thickness of 0.50mm. Specifically, untreated facing paper is pasted on an untreated base material.
[0093] The antibacterial and antiviral facing artificial board prepared in Example 1, the antibacterial and antiviral facing artificial board prepared in Example 7, and the artificial board without antibacterial and antiviral treatment in the comparative example were subjected to antibacterial and antiviral tests, and the analysis and test results are shown in the following table:
[0094] Table 1
[0095]
[0096]
[0097]
[0098] Table 2
[0099]
[0100]
[0101] The antibacterial performance test results are as follows
[0102] Table 3
[0103]
[0104] From the data in Table 1, Table 2, and Table 3, it can be found that the antibacterial and antiviral effects of Example 1 and Example 2 are very excellent, and the antibacterial rate can reach 99.99% for the three bacteria tested. The antiviral effects on human coronavirus and human influenza virus are both above 99%. In summary, the antibacterial and antiviral board has a good inhibitory effect on bacteria and viruses, while the untreated board has basically no inhibitory effect on the tested bacteria and viruses.
[0105] The present invention forms a novel composite antibacterial and antiviral agent by combining a variety of antibacterial and antiviral technologies. Compared with general antibacterial or antiviral plates, the antibacterial and antiviral plates have a synergistic effect, increasing the performance of a single antibacterial or antiviral function by 30%. At the same time, the present invention uses synergistic enhancement and porous nanostructures to make the antibacterial and antiviral components more evenly dispersed in the system, and reduces the consumption of active ingredients through ion replacement, thereby achieving the effect of sustained release of active ingredients and extending its antibacterial and antiviral time-effect life.
[0106] Although specific embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit thereof, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A composite antibacterial and antiviral sheet, characterized in that: The invention comprises two substrates (1), one end of each of the two substrates (1) is provided with a balancing layer (2), an adhesive (3) is provided between the two substrates (1) and the two balancing layers (2), and an antibacterial and antiviral impregnated decorative paper (4) is provided between the two balancing layers (2).
2. The composite antibacterial and antiviral agent ratio composition of the composite antibacterial and antiviral plate according to claim 1 is characterized by: The composite antibacterial and antiviral agent comprises the following components: nano silver zinc composite ion, polyhexamethylene guanidine hydrochloride, auxiliary antiviral agent, chitosan quaternary ammonium salt, stabilizer propylene glycol, nano porous structure aluminum silicate, and solvent deionized water. The proportion of the composite antibacterial and antiviral agent is as follows: nano silver zinc composite ion solution, the content is 2% to 5%, polyhexamethylene guanidine hydrochloride, the content is 10% to 20%, the auxiliary antiviral agent and chitosan quaternary ammonium salt content is 10% to 20%, the stabilizer propylene glycol content is 5% to 10%, the nano porous structure aluminum silicate content is 10% to 20%, and the solvent deionized water is the rest.
3. The method for preparing the nano silver-zinc composite ion solution in the composite antibacterial and antiviral agent of the composite antibacterial and antiviral plate according to claim 2, characterized in that: Silver nitrate, zinc sulfate, ammonium carbonate, ammonium bicarbonate, deionized water, and anhydrous ethanol are prepared to prepare a silver-zinc precursor, silver nitrate is dissolved in deionized water to obtain a silver nitrate solution, zinc sulfate is dissolved in deionized water to obtain a zinc sulfate solution, ammonium carbonate and ammonium bicarbonate are dissolved in deionized water to obtain a precipitation solution, further, the silver nitrate solution and the zinc sulfate solution are slowly added dropwise to the precipitant solution while stirring to react and generate a silver-zinc precursor precipitate, the silver-zinc precursor precipitate is washed 3 to 6 times with deionized water and anhydrous ethanol to remove impurities, and then the washed precipitate is The silver-zinc precursor powder is precipitated and dried in a vacuum drying oven to obtain a dry silver-zinc precursor powder. The dry silver-zinc precursor powder is further added to deionized water and stirred evenly to obtain a silver-zinc precursor solution. The silver-zinc precursor solution is further ultrasonically treated to uniformly disperse the silver-zinc precursor in the solution. The silver-zinc precursor solution after the ultrasonic treatment is heated to decompose the silver-zinc precursor to generate a nano-silver-zinc composite ion solution. The generated nano-silver-zinc composite ion solution is cooled and then diluted with deionized water to obtain a nano-silver-zinc composite ion solution of a desired concentration.
4. The method for preparing polyhexamethyleneguanidine hydrochloride in the composite antibacterial and antiviral agent of the composite antibacterial and antiviral sheet according to claim 2, characterized in that: Hexamethylenediamine and 36% hydrochloric acid are mixed in a certain ratio, the molar ratio of hexamethylenediamine to hydrochloric acid can be controlled between 1:2 and 1:2.
5. During the mixing process, hydrochloric acid should be added slowly to avoid violent reaction and local overheating. The mixed solution is heated to an appropriate temperature, the temperature is controlled between 60 and 80°C, the reaction time can be controlled within 3 to 5 hours, after the reaction is completed, the product is cooled, and then impurities are removed by 3 to 6 times of suction filtration and 5 to 10 times of deionized water washing. The product is dried to obtain polyhexamethyleneguanidine hydrochloride.
5. The method for preparing chitosan quaternary ammonium salt in a composite antibacterial and antiviral agent of a composite antibacterial and antiviral sheet according to claim 2, characterized in that: Chitosan, formaldehyde, formic acid and distilled water are sequentially added into a three-necked flask equipped with a condenser, wherein the mass ratio of chitosan, formaldehyde, formic acid and distilled water is 1:5:5:20, a magnetic stirrer is turned on, the speed is 100-700r / min, and the reaction is carried out at 50-80°C for 72 hours to obtain a light yellow solution, the obtained light yellow solution is subjected to reduced pressure distillation at 0.05-0.1MPa and 45-65°C for 30 minutes, and the pH value is adjusted to 10-13 with an alkaline solution. A large amount of gel is formed, which is then vacuum filtered at 0.05-0.1 MPa, washed with anhydrous ethanol until neutral, to obtain a light yellow gel-like substance, dried at 60-120°C, ground into a light yellow powder, dissolved with an acidic solution, and continued to add an acidic solution to adjust to a pH of 3-5, at which time a white precipitate can be obtained, washed with distilled water for 5-10 times, freeze-dried at -30 to -60°C, and ground the dried product to obtain chitosan quaternary ammonium salt.
6. The method for preparing nano-aluminosilicate in a composite antibacterial and antiviral agent of a composite antibacterial and antiviral sheet according to claim 2, characterized in that: The method comprises the following steps of: mixing tetraethyl orthosilicate, tetrapropylammonium hydroxide, sodium aluminate and water in a mass ratio of 45:5:1:120, placing the mixed system in a high-temperature hydrothermal reactor, wherein the volume of the mixed system accounts for 80%-85% of the total volume of the reactor, raising the temperature in the reactor to 175-185°C at a heating rate of 4-6°C / min, keeping the temperature for 4-6 hours, and naturally cooling to obtain a solid-liquid mixed system; centrifuging the solid-liquid mixed system at a rotation speed of 8000-10000 rpm for 5-10 minutes to obtain a sol clear liquid; spin coating the sol clear liquid on a clean glass surface at a spin coating speed of 2000-3000 rpm; drying the glass system coated with the sol, sintering it at 500-550°C for 1-3 hours, and naturally cooling to obtain a nano porous aluminosilicate film; and grinding to obtain a nano aluminosilicate powder.
7. The method for preparing a composite antibacterial and antiviral agent of a composite antibacterial and antiviral plate material according to claim 6, characterized in that: The following steps are involved: S1. Accurately weigh the prepared nano silver-zinc composite ion solution, polyhexamethyleneguanidine hydrochloride, chitosan quaternary ammonium salt, and nano aluminum silicate according to the formula ratio; S2, add to an appropriate amount of ionized water, stir at 60-80°C and 500-800 r / min for 240-300 min to fully dissolve and mix the components; S3, using a membrane method to filter the prepared composite product to remove impurities; S4, sterilizing the filtered solution to obtain the finished product of the composite antibacterial and antiviral agent.
8. The method for preparing the antibacterial and antiviral impregnated decorative paper of the composite antibacterial and antiviral sheet material according to claim 1, characterized in that: The preparation method of the antibacterial and antiviral impregnated decorative paper (4) is as follows: S1, add 5% by mass of curing agent to the melamine formaldehyde resin for impregnation with a solid content of 55% and a pH of 9.5, and stir quickly and evenly; S2. The decorative paper base paper is driven by the rotating roller of the impregnation machine. The rolling speed of the roller is 15 m / min. The decorative paper base paper is kept completely immersed in the first melamine formaldehyde resin impregnation. The base paper is then transferred to a drying oven. The oven temperature is adjusted to 110° C. S3, the rolling shaft is driven to the second impregnation tank, the antibacterial and antiviral agent is added to the melamine formaldehyde resin at a mass ratio of 0.5%, and the mixture is quickly stirred to be uniform, and the antibacterial and antiviral melamine formaldehyde resin for impregnation is prepared, the amount of glue is controlled to be 120g, and the decorative paper is kept completely immersed in the second impregnation, and then the mixture is driven to the drying oven for the second drying, the oven temperature is 130°C, and the mixture is dried for 10 minutes until the pre-curing degree is 40%; S4. After the second drying, adjust the oven temperature, dehumidify and cool to 50° C., control the total weight gain rate after two dips and drying to 110% of the base paper, cut and package according to the required size, and obtain antibacterial and antiviral decorative paper (4).
9. The method for preparing a composite antibacterial and antiviral board material according to claim 1, characterized in that: The preparation method of the substrate (1) is: S1, select blockboard substrate, moisture content 7.5%, size 2440mm*1220mm*17mm, balance layer (2) select technical wood veneer, thickness 0.50mm; S2, using the joinery board as the base material and the technical wood veneer as the balance layer, two finishing processes, the primary lamination method and the secondary lamination method, were used to prepare the antibacterial and antiviral impregnated film paper veneer joinery board; S3, 一 The second lamination process uses a glue spreading machine to coat the blockboard on both sides, with a glue spreading amount of 220-230g / ㎡ on each side, and the upper and lower sides are pressed with high-tech wood veneers, with a hot pressing temperature of 125℃, a hot pressing time of 9-10min, and a unit hot pressing pressure of 0.65-0.7MPa; after the hot pressing is completed, the antibacterial and antiviral impregnated film paper veneer is pressed, with a hot pressing temperature of 125-130℃, a hot pressing time of 6-7min, and a unit hot pressing pressure of 0.60-0.65MPa; S4, secondary lamination process, firstly, the antibacterial and antiviral impregnated adhesive paper and poplar veneer are hot pressed on one side, the hot pressing temperature is 190-200℃, the hot pressing pressure is 2.4MPa, and the hot pressing time is 15-20s; the glue machine coats urea-formaldehyde resin on both sides of the blockboard, the glue amount on each side is 220-230g / ㎡, the upper and lower layers of adhesive paper / poplar veneer composite are pressed, the hot pressing temperature is 90-95℃, the hot pressing time is 600s, and the unit hot pressing pressure is 0.65MPa.
Citation Information
Patent Citations
Preparation method of nano-silver antibacterial wood composite material
CN109591136A
Fragrance-releasing antibacterial and antiviral ecological board and preparation method thereof
CN115284693A
Method and device for manufacturing antibacterial and antiviral impregnated paper composite material
CN115928503A
Anion ecological plate
CN206374279U
Antibacterial porous beads and methods for preparing thereof
KR1020090117547A
Cited By
Impregnated bond paper with mildew-proof, antibacterial and antiviral effects and preparation process thereof
CN120537153A
Antibacterial cat and dog virus resistant pet plate and preparation method thereof
CN121798722A